Collaborative Governance Pentahelix and the Management of Sports Development in South Sumatra: Key Challenges and Future Potentials - Rudi Irawan; Alfitri Alfitri; Husni Thamrin; Andries Lionardo (ARISTO, 2026)
This article explores the evolution of sports policy in South Sumatra, focusing on athlete development and the challenges faced in the implementation process. South Sumatra has emerged as a key player in national sports, hosting prestigious international and national events, yet the province struggles with consistently producing top-performing athletes. The study examines the complexities of sports policy, including the role of government and private sector collaboration, and the impact of infrastructure and resource availability on athlete performance. It also highlights the disconnected between the large-scale investments in sports facilities and the declining achievements of local athletes. Key challenges identified include the lack of a comprehensive and cohesive policy framework, minimal private sector involvement, and inadequate athlete development programs. Through a review of the existing sports policies, this article aims to provide insights into how South Sumatra can improve its athlete development strategies to address these challenges. The findings emphasize the need for coordinated efforts between government, private stakeholders, and local communities to create a sustainable model for sports development in the province. Keywords: Collaborative Governance Pentahelix; Sports Policy; Athlete Development;